Bazaar, merchandise and decadence: Antonio José Ponte and Julián del Casal (Anclajes, 2021)
The fascination of Latin American modernism for 19th century French fashion merchandise has been widely addressed in literary theory. Texts filled with diverse cultural materials, textures and objects configured a poetics of the bazaar that became part of a series of strategies through which Latin American literature defined and linked itself to hegemonic aesthetics of the 19th century. The poems and chronicles of Cuban writer Julián del Casal (1863-1893) are no exception; this proliferation of merchandise reveals how the gaze and the images become configured as empty fictions, filled by a cosmopolitan desire. This feature, tied to the function and configuration of images in Cuban modernism, makes possible an anachronical reading of the presence of State merchandise at the other end of the century: Antonio José Ponte’s decadent reality in post-Soviet Cuba.
Keywords: Latin-American modernism; Cuban literature; merchandise; decadence